Does the oxygen tension of coronary sinus blood reflect myocardial oxygen tension? - Cicogna, A. C.; Tucci, P. J.; Spadaro, J.; Curi, P. R.; Lucchiari, P. H. (My University, 1989)
Coronary sinus blood oxygen tension (CSpO2) and myocardial oxygen tension (MpO2) were measured simultaneously during cardiac ischemia and reperfusion. Oxygen tension was measured using a polarographic method. Myocardial ischemia caused a reduction (5 +/- 1.5%; P less than 0.05) in CSpO2 and a decrease (56.5 +/- 10.1%; P less than 0.001) in MpO2. Reperfusion induced a rapid but transient increase (35.9 +/- 4.3%; P less than 0.001) in CSpO2 above the basal state while MpO2 returned gradually to the basal state. These results indicate that CSpO2 is of little value for the detection of changes in myocardial oxygen metabolism during the initial phase (seconds) of cardiac reperfusion.